2021
DOI: 10.1158/1940-6207.capr-20-0577
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health and Risk of Upper Gastrointestinal Cancers in a Large Prospective Study from a High-risk Region: Golestan Cohort Study

Abstract: Tooth loss and periodontal disease have been associated with several cancers, and poor oral health may be an important risk factor for upper gastrointestinal (UGI, i.e., esophageal and gastric) cancers. We assessed the relationship between oral health and UGI cancers using a large prospective study of over 50,000 adults living in Golestan Province, Iran, a high-incidence area for these cancers. Hazard ratios (HRs) and 95% confidence intervals (CI) were estimated for the association between three different meas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 51 publications
1
18
2
Order By: Relevance
“…Similar findings have been found in other high-risk areas such as Kashmir, India [ 72 ], Taixing, China [ 71 ], and Kenya [ 75 , 76 ], in addition to Japan [ 77 ] and parts of Latin America and Europe [ 78 ]. Regular tooth brushing has been shown to have a protective effect against ESCC in various studies [ 71 , 72 , 73 , 74 ]. Recent meta-analyses suggest an odds ratio (OR) of 1.3 to 1.5 comparing the highest versus lowest number of teeth lost [ 79 , 80 , 81 ] and an OR of around 0.60 when comparing high- versus low-frequency of tooth brushing [ 79 , 82 ] for overall EC risk (estimates were slightly weaker for tooth loss [ 79 , 80 ] and slightly stronger for tooth brushing [ 79 ] when the analysis was restricted to ESCC).…”
Section: Epidemiology Of Ecmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar findings have been found in other high-risk areas such as Kashmir, India [ 72 ], Taixing, China [ 71 ], and Kenya [ 75 , 76 ], in addition to Japan [ 77 ] and parts of Latin America and Europe [ 78 ]. Regular tooth brushing has been shown to have a protective effect against ESCC in various studies [ 71 , 72 , 73 , 74 ]. Recent meta-analyses suggest an odds ratio (OR) of 1.3 to 1.5 comparing the highest versus lowest number of teeth lost [ 79 , 80 , 81 ] and an OR of around 0.60 when comparing high- versus low-frequency of tooth brushing [ 79 , 82 ] for overall EC risk (estimates were slightly weaker for tooth loss [ 79 , 80 ] and slightly stronger for tooth brushing [ 79 ] when the analysis was restricted to ESCC).…”
Section: Epidemiology Of Ecmentioning
confidence: 99%
“…In fact, poor oral hygiene has been identified as one of the agents recommended for evaluation, with high priority for an upcoming IARC Monographs on the identification of carcinogenic hazards to humans [67]. Oral health-assessed by tooth loss; the sum of decayed, missing, or filled teeth (DMFT score); periodontal health; and oral hygiene practices (e.g., tooth brushing)-has been examined as a risk factor for ESCC in numerous epidemiologic studies [68][69][70][71][72][73][74][75][76][77][78]. A positive association between tooth loss and ESCC risk has been found repeatedly in both case-control and large-scale prospective cohort studies conducted in Linxian [68][69][70] and Golestan [73,74].…”
Section: Poor Oral Health As a Risk Factor For Ecmentioning
confidence: 99%
See 1 more Smart Citation
“…Several prospective cohort studies from the United Kingdom, the United States, and other Asian countries have demonstrated the association of oral health with gastrointestinal or related cancers 5 , 6 , 13 , 17 . This study supports these results with added perspective, as the relationship between oral health and gastrointestinal cancer was confirmed purely in community-dwelling older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Another prospective cohort study using data from the United Kingdom Biobank found that self-reported poor oral health (i.e., mouth ulcers, painful gums, bleeding gums, loose teeth, and toothaches) was associated with the incidence of hepatobiliary cancer 6 . Further, several other reports have shown that oral health indicators, such as tooth loss, periodontal disease, and poor oral hygiene, are associated with esophageal, stomach, colorectal, liver, and pancreatic cancers [7][8][9][10][11][12][13][14][15][16][17] . However, these relationships remain controversial because several studies reported contradictory results [18][19][20] .…”
mentioning
confidence: 99%